1989
DOI: 10.1111/j.1365-2621.1989.tb07935.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Simulated Sterilization of Particulate Solids in a Continuously Flowing System

Abstract: The heat transfer coefficients (h) between a cube and water were 239 and 303 W/m2K at 0 and 0.86 cm/s relative velocity. In 35% sucrose and 0 cm/set, h was 146 W/m*K. A model for heat lethality in cubes during continuous sterilization which used finite difference equations for heat conduction and above values of h, revealed that hold times for 6D inactivation of PA 3679 (F,=7.2 min) in an isothermal fluid at 132.2"C were 1.78 and 5.2 min for 1 and 2 cm cubes when h was 303 W/m2K and 1.23 and 4.13 min when h wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 1 publication
4
43
1
Order By: Relevance
“…Most of the existing research particularly that reported in process engineering literature has been conducted at much higher Reynolds numbers. Chang and Toledo (1989) observed that when the relative velocity between particle and fluid is the same as the velocity of the fluid past a stationary particle, the heat transfer coefficients should be similar in both the cases. The fluid to particle heat transfer coefficient was found to increase with increasing slip velocity (Balasubramaniam and Sastry 1994).…”
Section: Background and Scopementioning
confidence: 88%
“…Most of the existing research particularly that reported in process engineering literature has been conducted at much higher Reynolds numbers. Chang and Toledo (1989) observed that when the relative velocity between particle and fluid is the same as the velocity of the fluid past a stationary particle, the heat transfer coefficients should be similar in both the cases. The fluid to particle heat transfer coefficient was found to increase with increasing slip velocity (Balasubramaniam and Sastry 1994).…”
Section: Background and Scopementioning
confidence: 88%
“…In continuous aseptic processing of particulates, Chang and Toledo (1989) demonstrated that non-isothermal conditions exist and h and k may not be combined to accurately simulate the lethal effects of heat during the process. h is dependent on geometry and relative fluid velocity while k is temperature dependent.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional thermal process calculations, the heating medium is at a constant temperature, therefore, the effects of h and k may be combined as an apparent (Y or in the expression for fh. In continuous aseptic processing of particulates, Chang and Toledo (1989) demonstrated that non-isothermal conditions exist and h and k may not be combined to accurately simulate the lethal effects of heat during the process. h is dependent on geometry and relative fluid velocity while k is temperature dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal properties of the surrounding fluid are less critical for heat transfer to particles since the heat transfer coefficient, h (cal/s-cm 2 −°C), between the fluid and particle is limiting [59]. Its effectiveness is shown by the Nusselt number (ratio of total heat transfer to conductive heat transfer), N Nu , given by hD p / K , where D p (cm) is the particle diameter, and K (cal-cm/s-cm 2 −°C) is the thermal conductivity of fluid at the processing temperature [22, 49]. If the predicted particle temperature profile is hotter than the actual one, it is possible to obtain incomplete inactivation [20].…”
Section: Introductionmentioning
confidence: 99%